495. Effectiveness of Personal Protective Equipment in Preventing Transmission of COVID-19 in Healthcare Workers. (31st December 2020) - Li, Aldon; Rieg, Gunter; Maldonado, Ana Miranda; Concepcion, June
Abstract: Background: Human-to-human transmission of the SARS-CoV-2 occurs during exposure to infectious respiratory particles generated by humans with COVID-19. Global personal protective equipment (PPE) shortages necessitate further studies looking at the correlation between PPE use and transmission of COVID-19 to healthcare workers (HCW). This study aims to provide data on test positivity rates of HCW wearing different PPE. Methods: Retrospective Case Series. During the study period from Mar-Apr 2020, HCW were tested for SARS-CoV-2 if they 1) were exposed to COVID-19 case OR 2) had symptoms of potential COVID-19 disease per CDC criteria. Respirator masks defined as N95 or higher were used in high risk departments (Emergency and Urgent Care (ERUC), Medical/Surgical (MSU), and Intensive Care (ICU) units). Medical masks defined as surgical or procedural masks were used in low risk, outpatient departments. All departments used gowns, gloves, eye protection, and appropriate masks. Results: In low risk departments, 124/1578 (7.9%) of HCW tested positive, compared to 118/1499 (7.9%) of HCW who worked in high risk departments (p=0.9886). In high risk departments, 55/626 of HCW who worked in MSU, 37/459 of HCW who worked in ERUC, and 26/414 who worked in ICU tested positive. In a logistic regression model comparing tested individuals in high risk departments to those in ambulatory settings, a slightly lower risk of a positive test among ICU employees (OR=0.786, CI=0.508–1.217) was found, and a similar risk among ERUC employees (OR=1.028, CI=0.701–1.508) and MSU employees (OR=1.129, CI=0.810–1.574) was found, but the differences were not statistically significant (p=0.5364). Conclusion: HCW in ambulatory settings who used medical masks did not test positive at a higher rate than providers in high risk departments using respirators. The slightly lower positive rate in ICU providers may suggest respirator masks are beneficial in settings with higher risk of aerosolizing generating procedures, or it maybe related to training and familiarity with infection control procedures. The level of mask used was equally appropriate across all risk level care settings, providing evidence for local strategies to optimize PPE stewardship based on department assignments while protecting HCW during the COVID-19 pandemic. Disclosures: All Authors : No reported disclosures